Kidney cancer and 2014: is innovation really over?. (May 2015) - Ciccarese, Chiara; Modena, Alessandra; Tortora, Giampaolo; Massari, Francesco
ABSTRACT : 2014 has been a year of significant innovations on kidney cancer treatments, the most relevant of which will be shown below. In particular, we analyzed the consolidated knowledge regarding the role of surgery in localized and advanced renal cell carcinoma and the targeted therapies already approved for metastatic renal cell carcinoma. Furthermore, we examined the outstanding issues, with particular reference to the choice of the second-line and the role of adjuvant and neoadjuvant treatments. Finally, we outlined the future therapeutic perspectives and those definitely abandoned.